Dazzle - Gould, Judith (New York : Onyx, 1989)
Three generations of independent and dauntless women experience turbulent personal and love lives as they make their mark in Czarist Russia, 1930s Hollywood, and the Middle East of the 1980s.
National College of Business and Arts
Keywords: Love stories